A Hyperlink based Graphical User Interface of Knowledge Management System for Broiler Production - Yusra Fernando; Kudang Boro Seminar; Irman Hermadi; Rudi Afnan (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The level of consumption of animal protein in Indonesia has been increasing. Unfortunately, this increase has not been balanced by the adequate rise stock production.  The use of closed house system for broiler production is very potential to contribute the increase of protein source. The purpose of this research is to build a knowledge management system broiler production management closed house system. Web-based system developed using PHP programming language, and Protégé as processing knowledge representation. This research has developed the concept of knowledge management system with ontology model of semantic network, among the results of this research is a conceptual model, knowledge maps, and prototype production management knowledge management website broiler closed house system. Knowledge management system is equipped with recording system applications. This application is useful to be able to see results in the production of a period of production. The prototype knowledge management website provides links consultancy services for farmers who want to ask about production management. The concept of knowledge management systems can be used as a basis for building a semantic website that can model the process and rules management broiler production closed house system.